The 21st century corporate town: The politics of planning innovation districts. (November 2020) - Heaphy, Liam; Wiig, Alan
Highlights: Waterfront redevelopments projects are increasingly linked to innovation districts. The innovation district model has facilitated tech sector driven smart urbanism. This form of urbanism has a limited engagement with place and heritage. Smart urbanist waterfront projects herald the arrival of the 'corporate town'. Abstract: High-tech corporations have established a foothold in cities through innovation districts. Across the north Atlantic, these are typically waterfront urban renewal projects that repurpose formerly industrial land contiguous to the city centre into fully master-planned sites that also include smart city developments. Our case study focuses on the governance and spatial planning of waterfront innovation districts in Boston in the United States and Dublin in Ireland. Both cases reflect a trend to create high-value clusters attracting research and development from globalised tech firms as well as fostering local enterprise. The fluidity and mobility of multinational capital attached to the tech economy leverages digital and civic investment in these districts as a means of corporate attraction and retention: the smart city becomes one for skilled, globally-mobile tech workers adjacent to, but socially and spatially partitioned from, historically working class port communities. This process is marked by the degree to which such districts can be, firstly, disconnected from city-wide planning agendas, and secondly, the degree to which they interface and share resources and amenities with surrounding neighbourhoods. Thus, we argue, there is the potential for further market capture of urban revitalisation policies by high-tech firms, leading to the creation of 'corporate towns' and a new era of uneven development. The politics of urban planning can both restrict the democratic process in the city, and curtail the forms of smart city, civic technologies into those primarily beneficial for high-tech corporations and their workforce.